Colonic motility in ulcerative colitis. Issue 6 (December 2014) - Bassotti, Gabrio; Antonelli, Elisabetta; Villanacci, Vincenzo; Baldoni, Monia; Dore, Maria Pina
Background: Inflammatory conditions affecting the gut may cause motility disturbances, and ulcerative colitis – one of the main disorders among the inflammatory bowel diseases – may display abnormal colonic motility. Aim: To review the abnormalities of the large bowel in ulcerative colitis, by considering the motility, laboratory (in vitro) and pathological studies dealing with this topic. Methods: A comprehensive online search of Medline and the Science Citation Index was carried out. Results: Patients with ulcerative colitis frequently display colonic motor abnormalities, including lack of contractility, an increase of propulsive contractile waves, an excessive production of nitric oxide, vasoactive intestinal polypeptide nerves, interleukin 1 beta, neurotensin, tachykinins levels and the weaker action of substance P, likely related to a neuromuscular dysfunction due to the inflammatory process. Conclusions: A better understanding of the pathophysiological grounds of altered colonic motility in ulcerative colitis may lead to a more in-depth knowledge of the accompanying symptoms and to better and more targeted therapeutic approaches.